CRISPR/Cas12a-assisted rapid identification of key beer spoilage bacteria. (December 2021) - Meng, Qingzhou; Yang, Hongmei; Zhang, Guiquan; Sun, Wenjun; Ma, Peixiang; Liu, Xinyi; Dang, Lu; Li, Guanglei; Huang, Xingxu; Wang, Xinjie; Liu, Jianghuai; Leng, Qibin
Abstract: Beer spoilage bacteria present severe challenges for the beer fermentation industry. Here, we establish a rapid, specific and highly portable CRISPR/Cas12a-based key beer spoilage bacterial scanning method, dubbed CRISPR-Beer Scan. With the variable 16S rDNA segments of these major spoilage microbe species serving as targets, highly efficient and specific crRNAs were determined. By coupling with recombinase polymerase isothermal amplification, CRISPR-Beer Scan could detect as low as 10 copies of DNA targets. Indeed, trace amounts of target genome DNAs can be accurately identified within a mixture of genome DNAs conditioned in beer. Moreover, the extracted genome DNA samples can be conveniently distinguished through the visual fluorescent signals excited by blue light in 45 min with CRISPR-Beer Scan Method. Taken together, the CRISPR-Beer Scan represents a widely applicable microbe-monitoring platform for not only breweries, but also other industries. Highlights: For the first time, CRISPR/Cas12a-based nucleic acid detection was used to detect key beer spoilage bacteria: Lactobacillus brevis, Lactobacillus lindneri and Pediococcus damnosus . This assay could detect as low as 10 copies of DNA targets specifically. Operation of this assay is very convenient and finished in 45 min once the genome DNA were extracted.